Three new species of the subgenus Jaynesia Allen, 1969 of the genus Tiphia Fabricius, 1775 (Hymenoptera: Tiphiidae: Tiphiinae) from China, with a key to all known species - Han, Qian; Chen, Bin; Li, Ting-Jing (Zootaxa, 2021)
In this study, three new species of the subgenus Jaynesia Allen from China are described and illustrated, namely T. hohehotensis sp. nov. from Inner Mongolia, T. displicata sp. nov. from Sichuan, and T. rotunda sp. nov. from Gansu. A key to all known species of Jaynesia is also provided.